Noncanonical effects of vasopressin in angiogenesis - I. I. Khegay (Вавиловский журнал генетики и селекции)
The molecular action of vasopressin depends on the localization of hormonal receptors. The basic physiological effects of vasopressin are manifested in the blood vasculature, renal inner medulla and brain. To date, new information concerning the tissue-specific spreading of vasopressin receptors has been accumulated, and it needs to be summarized. Platelets and endotheliocytes expressing V1a and V2 receptor types, respectively, are related to less investigated targets of the hormone. Vasopressin induces the initial reversible stage of platelet activation, required for interaction with intercellular matrix proteins. Platelet adhesion on endothelium activates cellular secretion of growth factors and enzymes for intercellular matrix glucosamine metabolism. Platelet hyaluronidase HYAL2 hydrolyses high-molecular hyaluronic acid to shorter fragments. Unlike intact hyaluronic acid with a molecular weight of several megadaltons, generally showing distinctive antiangiogenic properties, intermediate fractions of hyaluronan hydrolysis in a range from 2.5 to 200 kilodaltons have a stimulating effect on angiogenesis. Intercellular contacts between platelets and endotheliocytes are stabilized due to adhesive transmembrane glycoprotein PECAM-1 interaction. Resulting PECAM-1 heterodimers acquire conformation with high affinity to integrins αvβ3. Integrin activation forms contact links between endothelium and fibrillar proteins. Activated endotheliocytes secrete von Willebrand factor and P-selectin. These proteins are accumulated in Weibel–Palade bodies. Vasopressin stimulates cAMP-dependent ACAP-regulated exocytosis of Weibel–Palade bodies. von Willebrand factor possesses adhesive properties and additionally accelerates interaction of cells with the intercellular matrix. Adhesion on fibrillar collagen and membrane glycoproteins in cooperation with effects of PECAM-1–αvβ3 integrin complexes fixes cell aggregates in the surrounding interstitium and promotes proliferating endotheliocyte migration in according to the direction of local growth factor gradients during angiogenesis. Neurohormonal regulation of platelet and endotheliocyte secretory activity functionally link proliferation and migration of endotheliocytes during angiogenesis and integrate it according to the adaptive capacity of the entire organism.